6g+3g-10+3=47

Simple and best practice solution for 6g+3g-10+3=47 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6g+3g-10+3=47 equation:


Simplifying
6g + 3g + -10 + 3 = 47

Reorder the terms:
-10 + 3 + 6g + 3g = 47

Combine like terms: -10 + 3 = -7
-7 + 6g + 3g = 47

Combine like terms: 6g + 3g = 9g
-7 + 9g = 47

Solving
-7 + 9g = 47

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 9g = 47 + 7

Combine like terms: -7 + 7 = 0
0 + 9g = 47 + 7
9g = 47 + 7

Combine like terms: 47 + 7 = 54
9g = 54

Divide each side by '9'.
g = 6

Simplifying
g = 6

See similar equations:

| -6x+5(-x+8)=139 | | 15(16)-14=c | | h+13.5=-13.5 | | 15(10)-14=c | | 15(2)-14=c | | 4x-9=4x+12 | | -8=3u-5 | | 10y-3y=7 | | (X+2)(x+10)=20 | | -2+9=1x+42 | | 7t+1+5t+8=162 | | -8v+3(v+8)=29 | | -45+15(x)=0 | | -45+15(0)=x | | 4x^3+10x^2-4x-10=0 | | y=-23000+4500x | | -7g=10-6g | | 3x-2y=4x | | -2v-6v=-16 | | 0=4e+4 | | 36-3x=312-x | | 7t+1=162 | | 2x-3+21=-3 | | -45+15(15)=x | | y=2000+2500x-25000+2000x | | 2-(x-3)+6=8 | | 5n+9=54 | | -45+15(1)=x | | a-7a+3=6a+3 | | 1+3n+6=-5 | | (3+3i)+(2+4i)= | | -7w(w-2)=5(3-w) |

Equations solver categories